The effect of the dietary approaches to stop hypertension diet on total antioxidant capacity, superoxide dismutase, catalase, and body composition in patients with non-alcoholic fatty liver disease: a randomized controlled trial - Zare, Zahra; Hosseinzadeh, Mahdieh; Sharuni, Fatemeh; Rohani, Fatemeh Sadat; Hojjat, Hashem; Rahimpour, Shahab; Madadizadeh, Farzan; Zavar Reza, Javad; Wong, Alexei; Nadjarzadeh, Azadeh (Frontiers in Nutrition, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a condition characterized by the accumulation of fat in the liver without excessive alcohol consumption. Lifestyle modifications, such as adopting a healthy diet, represent the standard treatment for NAFLD. However, the impact of the Dietary Approaches to Stop Hypertension (DASH) diet on oxidative stress biomarkers in patients with NAFLD remains unclear. Therefore, the aim of this study was to determine the effect of the DASH diet on total antioxidant capacity (TAC), catalase (CAT), superoxide dismutase (SOD) levels and body composition in overweight and obese patients with NAFLD. A total of 70 overweight and obese patients aged 18-70 years were randomly assigned to either the intervention (DASH diet, n = 35) or the control group (control diet, n = 35) for 12 weeks, with both groups following a calorie-restricted diet. The mean age of participants was 43.1 ± 8.1 years in the DASH group and 45.1 ± 8.6 years in the control group. At the end of the study, a significant difference was observed in the mean TAC and SOD levels between the two groups (p = 0.02). After adjusting for potential confounding factors, such as age, sex, diabetes, smoking, physical activity, and baseline values, the DASH diet maintained its significant effects on TAC and SOD compared to the control diet (p = 0.03). However, there were no significant differences in CAT levels between the two groups. Moreover, a significant reduction in visceral fat (p = 0.01) and a marginally significant decrease in BMI (p = 0.06) were observed in the DASH group compared to the control group, after adjusting for potential confounders. In conclusion, our study showed that following the DASH diet for 12 weeks in overweight and obese patients with NAFLD has beneficial effects on TAC, SOD, and visceral fat. These findings support the use of the DASH diet as a potential therapeutic intervention for the improvement of oxidative biomarkers in patients with NAFLD.